EARLY LITERACY: REFLECTIONS ON STROKES AND SOUNDS - Juan Esteban Valoyes Orozco; Daliris Arrieta Soto (DIALÉCTICA, 2026)
This essay critically examines the neurocognitive, pedagogical, and sociocultural obstacles inherent in the acquisition of early literacy skills; a process that transcends simple decoding to become a reconfiguration within the cerebral cortex. A documentary review methodology was used; the objective corresponds to examining the transition that, for the purposes of this study, has been termed: early literacy: reflections from strokes and sounds: problems that affect the process. The results highlight the difficulties present in literacy, which often arise from a disconnect between the child’s biological maturity and the teacher’s mediation in the teaching activity, specifically in implementing the curriculum requirements. In this regard, resolving these problems requires ethical teaching practices grounded in neuroeducation, which value errors from a learning perspective. It is recommended to implement strategies and programs for the systematic stimulation of phonological awareness. This essay aimed to provide a holistic perspective to ensure students’ ability to find, use, create, evaluate, and communicate information effectively and efficiently through digital technologies, with teacher guidance. The goal is to achieve functionality and equity by promoting children’s genuine inclusion in the knowledge society within their educational context, ensuring that each stroke represents a reflective action that demonstrates independent and critical thinking.